RESISTIVE INDEX ON DOPPLER ULTRASOUND AFTER RENAL TRANSPLANTATION AS RENAL FUNCTION PREDICTOR: Doppler Ultrasound After Renal Transplantation - Khan, Sara; Nayyar, Bushra; Baloch, Salahuddin (Pakistan Armed Forces Medical Journal, 2015)
Objective: To determine the correlation between doppler resistive index and serum creatinine levels in renal transplant recipients.Study Design: Cross sectional study.Place and Duration of Study: Department of Radiology, Military Hospital Rawalpindi from Oct 2009 to Oct 2010.Patients and Method: A total of 82 outdoor and admitted patients of both genders, within age group of 18-60 years, were included in the study. These patients were referred from Nephrology department Military Hospital, Rwp and Armed Forces Institute of Urology after renal transplant. Written informed consent was taken alongwith history of any co-morbid disease like dabetes or hypertension and for post transplant duration. Gray scale ultrasound was performed first, followed by doppler ultrasound of transplanted kidney and resistive index was calculated. The presence of any post transplant complications were also recorded. The values of resistive index were then correlated with the serum creatinine levels.Results: Doppler ultrasound was performed on 82 patients included in the study and resistive index was calculated. A strong correlation between resistive index (RI) and serum creatinine level was found as calculated through Pearson’s equation i-e 0.89. Thus making resistive index a strong predictor of transplanted kidney function and survival. Patients with RI>0.8 were older with mean age of 45.56, had raised serum creatinine level with mean value of 276.69µmol/l and had longer post transplant duration (mean 21.63 weeks). These patients also had other co-morbid diseases like diabetes mellitus and hypertension. The commonest post transplant complication was raised parenchymal echogenicity (30.5%), followed by perinephric collections (18.3%).Conclusion: RI on doppler ultrasound in renal transplant patients shows a strong correlation with serum creatinine levels.  Renal transplant patients with elevated serum creatinine levels had raised resistive indices.